Improving the Quality of Life by Utilizing Social Media as a Media for Marketing Activity Therapy Product of Breast Cancer Survivor in Medan City - Hasnida; Lubis, Namora Lumongga; Lubis, Ramona Dumasari; Novitarum, Lilis (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Breast cancer survivors have a desire to remain productive in helping the family's economic function. As housewives, breast cancer survivors have free time that can be used to earn income. Moreover, at this time, easy access to information through social media is one way to market their handicraft products. However, this is still not the main focus of the group. Considering that the average age has passed the age of 50, their ability to use social media is still very lacking. Whereas with survivors having positive activities, they are expected to increase their motivation and quality of life. The purpose of this community service is to improve the quality of life of survivors by preparing breast cancer survivors to be able to independently produce handicrafts and market them digitally through social media. Activities carried out using training and mentoring methods in using social media as an effective marketing medium. After providing assistance in uploading handicrafts to social media by using services to expand their reach, the interest of buyers began to increase and the sales of handicrafts began to increase.